Leadership styles of headteachers and their impact on students’ academic performance in secondary schools, Nyamaiya Division, Nyamira District, Kenya - Nyagaka, Evans; Ajowi, Jack O. (Mediterranean Center of Social and Educational Research, 2013)
The nerve centre of this study was that despite the critical role played by the head teacher in secondary school management, students’ academic performance has persistently been poor. Factors leading to this dismal performance have not been adequately investigated and well understood in Nyamaiya Division hence the need for this study. Therefore, the purpose of this study was to determine the leadership styles of the headteachers and their impact on the students’ academic performance in KCSE secondary schools in Nyamaiya Division, Nyamira District. The study was conducted in six secondary schools within Nyamaiya Division, Nyamira District from population of 15 schools, hence six headteachers, and 72 teachers from population of 180 and 680 students from population of 1700. The interest of the researcher to choose and study these schools is strongly prompted by their continued poor performance in KCSE. Data was collected using the questionnaires and interview schedules. The study used descriptive statistics such as percentages and frequency, which were used concurrently with the Chi-Square test in the analysis. The study intended to come up with policy guidelines that were to help improve the leadership styles of head teachers in Kenya and other developing countries, which require similar policies. The study was further to contribute to the functions of knowledge for the present and future scholars. The major findings show a significant relationship between initiative structures of the head teachers towards improving leadership style which has impact on academic performance, it further shows no significant relationship between consideration behavior of the head teachers regarding day to day issues which has impact on academic performance and finally there was a strong relationship between participatory traits of the head teachers and the management structures of the schools which has impact on the students’ academic performance. Based on these findings, it is recommended that to the school administration to cooperate from parents by holding regular meetings and working out strategic plans, to the ministry to in-service headteachers through workshops and finally to the teacher to be encouraged occasionally to review their own leadership styles and check their impact on students’ academic performance.
DOI: 10.5901/jesr.2013.v3n3p157
Keywords: Head teacher leadership styles; Students’ academic performance administration